Gut Microbiota Characteristics in Children After the Use of Proton Pump Inhibitors - Simakachorn, Lila; Tanpowpong, Pornthep; Chanprasertyothin, Suwanee; Thongpradit, Supranee; Treepongkaruna, Suporn (Turkish Journal of Gastroenterology, 2021)
Background/Aims: Prolonged acid suppression from proton pump inhibitor (PPI) has been shown to cause gut microbiota alteration which may increase risk of various infections in adults. We aimed to characterize gut microbiota profiles in children after a short-term use of PPI.Materials and Methods: Children aged 1-18 years who underwent PPI therapy were included during April-December 2017. We excluded children who previously used antibiotics or acid suppressants, had a history of acute gastroenteritis or specific food avoidance one month prior to the enrolment. The stool samples before and after the PPI use were collected for gut microbiota composition. The 16S ribosomal RNA gene sequencing was performed by using Illumina MiSeq. The differences in gut microbiota profile after the use of PPI were compared to pre-PPI period.Results: We completed stool collection in 20 children (median age of 5.8 years and 60% were female). No significant changes in the overall number of species-level taxonomy categories or predominant bacteria phylum (Bacteroidetes) were noted. We found a trend increase in the proportion of phylum Firmicutes among children living in the metropolitan/suburban area (P=.07) and among males (P=.11). In four children with infection-related adverse effects, we noted a non-significant increase in the proportion of phylum Firmicutes after the PPI use (from 35 to 52%, P = .14). Conclusion: Even the total number and predominant gut microbiota did not significantly change after a four- to eight-week course of PPI therapy; we found a trend of increased proportion of phylum Firmicutes in certain groups of children.